Building Cooperative Character Through the Traditional Game of Gobak Sodor - Kurnia, Salsa Hilda; Sucipto Djiwo, Al-Qudus Nofiandri Eko (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Traditional games play a crucial role in shaping children's character, particularly in fostering cooperative values. This study aims to explore how cooperative values are applied through the traditional game of Gobak Sodor. Using a qualitative descriptive approach, data were collected through documentation, observation, and in-depth interviews. The data were analyzed using Miles and Huberman's interactive analysis model, encompassing data reduction, data presentation, and conclusion drawing. The findings reveal that Gobak Sodor significantly enhances cooperative values through active interactions in coordination, communication, and team strategies. Furthermore, the game promotes the development of other character values, such as honesty, discipline, and responsibility. These findings highlight that Gobak Sodor can be utilized as an effective and enjoyable method for character education in children.